2014
DOI: 10.4236/as.2014.513142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glyphosate Formulations for Weed Control and Tolerance in Maize (<i>Zea mays</i> L.) and Soybean [<i>Glycine max</i> (L.) Merr.]

Abstract: Twenty-two field experiments (six maize (Zea mays L.) and five soybean [Glycine max (L.) Merr.] using low glyphosate doses to assess weed control and six maize and five soybean using high glyphosate doses to assess tolerance) were conducted from 2010 to 2012 at two locations in southern Ontario, Canada to compare the commercially available glyphosate formulations of Roundup Weather MAX ® , Clearout ® 41 Plus, and Wise Up ® (WeatherMAX, Clearout, and WiseUp, respectively). In maize and soybean, control of velve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The "generic" dummy controls for the possibility that farmers perceive generic products as less effective and therefore compensate by increasing application rates. Although peer-reviewed studies find no significant differences in efficacy between generic and non-generic products (Hartzler, Pringnitz, and Resfell, 2002;Mahoney, Shropshire, and Sikkema, 2014), anecdotal evidence via web-based forums suggests that some farmers are wary of generic products, particularly those not produced in the United States. 7 As noted, previous work has shown that some individuals are willing to purchase non-generic medications at a price premium, despite having the same ingredients.…”
Section: Empirical Methodsmentioning
confidence: 99%
“…The "generic" dummy controls for the possibility that farmers perceive generic products as less effective and therefore compensate by increasing application rates. Although peer-reviewed studies find no significant differences in efficacy between generic and non-generic products (Hartzler, Pringnitz, and Resfell, 2002;Mahoney, Shropshire, and Sikkema, 2014), anecdotal evidence via web-based forums suggests that some farmers are wary of generic products, particularly those not produced in the United States. 7 As noted, previous work has shown that some individuals are willing to purchase non-generic medications at a price premium, despite having the same ingredients.…”
Section: Empirical Methodsmentioning
confidence: 99%
“…adjuvants or salts), each glyphosate formulation is expected to infl uence the rate of uptake and translocation directly, and consequently, the activity of the herbicide (REIS et al, 2014). In this respect, while some reports showed that at least one glyphosate formulation was involved in the occurrence of undesirable eff ects in RR soybean, particularly visible damage (MAHONEY et al, 2014), other studies revealed that the type of glyphosate formulation was unrelated to the occurrence of adverse any eff ects in the crop (ALBRECHT et al, 2018) or in RR2 maize (MAHONEY et al, 2014). For these studies, damage was more related to increases in the rate of glyphosate than the type of formulation.…”
Section: Introductionmentioning
confidence: 99%